ANALISIS TRANSAKSI IJON BUAH MUSIMAN DITINJAU DARI PERSPEKTIF HUKUM ISLAM DI DESA SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Ridwan Harahap; Ahmad Shirotol; Ratih Febriyani; Muhammad Selamat (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Analysis of Seasonal Fruit Bonded Transactions Viewed from an Islamic Law Perspective in Selatbaru Village, Bantan District, Bengkalis Regency". In preparing this thesis, the author only limited it specifically to Selatbaru Village, because the author wanted to measure and examine problems regarding bonded transactions carried out by the people of Selatbaru Village and how Islamic law applies to bonded transactions. This research is field research using qualitative methods with data collection using interviews and documentation. Data analysis techniques use data reduction, data presentation and verification and conclusions. The results of the research show that: (1) The seasonal fruit bonded transaction procedure in Selatbaru Village is that bonded transactions are diverse and varied, but in general bonded debt is a form of tree rental from which the benefits are taken, namely in the form of fruit while the fruit is still on the tree. This practice of ijon is included in the prohibited type of buying and selling, namely Ba'i Al-Mukadhrah, namely selling fruit that is not yet ready to be harvested, such as selling durian, rambutan and fines that are still young/green nipples. (2) Islamic law regarding ijon is very clear that this ijon transaction is prohibited and invalid because in this transaction there is an element of gharar (uncertainty) both in the quantity and quality of the ijon transaction, so that the terms of mutual consent may not be fulfilled and can harm one of the parties. party. Bonded buying and selling is invalid and void by law because it does not fulfill the objective requirements of the agreement and in Islamic law it is not permitted because it contains elements of gharar (uncertainty) and maysir (gambling) and is included in urf because it is contrary to sharia.